2001
DOI: 10.1097/00005373-200109000-00009
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of Adolescent Trauma Admitted to an Adult Surgical Intensive Care Unit versus a Pediatric Intensive Care Unit

Abstract: Adolescent trauma patients admitted to the PICU were less likely to be intubated or have a Swan-Ganz catheter placed. They had decreased LOS and days of mechanical ventilation. There was no difference in outcome measurements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…Coresidence may influence the quality and intensity of care for children, as indicated in a prior study that showed shorter severity-adjusted lengths of stay and fewer days of mechanical ventilation for adolescent trauma victims admitted to a PICU, compared with an adult surgical ICU. 19 Although the number of coresident PICUs is small now, the phenomenon of coresidence warrants additional investigation, because constrained fiscal or staffing resources may force some smaller facilities that have separate PICU beds currently to consider coresidence in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Coresidence may influence the quality and intensity of care for children, as indicated in a prior study that showed shorter severity-adjusted lengths of stay and fewer days of mechanical ventilation for adolescent trauma victims admitted to a PICU, compared with an adult surgical ICU. 19 Although the number of coresident PICUs is small now, the phenomenon of coresidence warrants additional investigation, because constrained fiscal or staffing resources may force some smaller facilities that have separate PICU beds currently to consider coresidence in the future.…”
Section: Discussionmentioning
confidence: 99%
“…This might be attributable to several causes, including the expertise of medical staff treating critically ill children. According to prior studies, a lack of specialist medical staff in PICU increases the number and duration of treatments such as mechanical ventilation, central catheterization, and urinary catheterization, leading to an increase in hospital‐acquired infections . In this study, all patients were cared for by a pediatrician.…”
Section: Discussionmentioning
confidence: 99%
“…This principle also applies to a child with major injuries. Reports from the USA indicate that a tiered system of management improves outcome 12,16 and the London Severe Injuries Group proposed a three-tier triage system for trauma services in London, which draws attention to the need for triage guidelines (H. Phillips, personal communication)…”
Section: Discussionmentioning
confidence: 99%
“…For less severely injured children, other factors are taken into consideration, including the mechanism and severity of injury, the nature of the injuries and the age of the child. The services and facilities available at each hospital are also relevant 11,16 .…”
Section: Discussionmentioning
confidence: 99%